PERILAKU APARATUR SIPIL NEGARA PADA BAGIAN HUBUNGAN MASYARAKAT SEKRETARIAT DAERAH KABUPATEN PARIGI MOUTONG - Simpu, Astiti H. (Katalogis, 2017)
The main subject of this study is the behavior of public servant employees. This study aims at finding out the behavior of public servant employees of public relation division of regional secretariat of Parigi Moutong Regency. The theory used is theory of Bureaucracy by Miftha Thoha that formulated in five aspects: Capabilities, Needs, Trust, Experiences and Expectations.This research usedqualitative method. The informants are official employees and staff public relation division of regional secretariat of Parigi Moutong Regency that taken by purposive sampling technique. Technique of data collection Â consisted of observation, interview and documentation while technique of data analysiswere data reduction, data presentation, and conclusion (verification). The results shows that the behavior of public servantemployee in public relation division of regional secretariat of Parigi Moutong Regencyhas not conducted fully by Bureaucracy apparatur. It can be seen from the Individual Characteristics. Only aspect of capability, trust and experience run well.Meanwhile, need and expectation have not been fully carried out. The ability of personnel in public relation division is categorized as good enough, but they lack of discipline in terms of office hours. In fact, good individual ability should be in harmony with good discipline. Furthermore, Â in line with the aspect of needs, individuals behave differently because of the different individual needs background, but in order to achieve organizational goals, employees in public relations division have the same orientation to achive organizational goals. Regarding to the aspect of trust, each staff in public relations division gets egual trust from the leader. Each employee who break the trust given by the leader are going to recieve directly either verbal or written reprimand. In relation to the aspect of work experience, each employee of public relation division is basically good, but they must always be given guidance. For those who complete the task properly, need to be given reward while those who are negligent penalties should be applied. Therefore, the leader needs tocreate work plans that lead to the fulfillment of those needs. Last but not least, the aspect of expectations in public relation division has not been entirely fulfilled. Therefore, leaders should plan to increase those capabilities to a variety of training or technical assistances.